2017
DOI: 10.1016/j.kint.2017.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker research to improve clinical outcomes of peritoneal dialysis: consensus of the European Training and Research in Peritoneal Dialysis (EuTRiPD) network

Abstract: Peritoneal dialysis (PD) therapy substantially requires biomarkers as tools to identify patients who are at the highest risk for PD-related complications and to guide personalized interventions that may improve clinical outcome in the individual patient. In this consensus article, members of the European Training and Research in Peritoneal Dialysis Network (EuTRiPD) review the current status of biomarker research in PD and suggest a selection of biomarkers that can be relevant to the care of PD patients and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 112 publications
3
51
0
Order By: Relevance
“…Medicine treatment and ALB more than 35 g L −1 were beneficial for technical survival. Consistent with other previous reports, our study showed that cardiac events were the main cause of death [ 16–18 ] and peritonitis occurring during the peritoneal dialysis must be taken seriously [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Medicine treatment and ALB more than 35 g L −1 were beneficial for technical survival. Consistent with other previous reports, our study showed that cardiac events were the main cause of death [ 16–18 ] and peritonitis occurring during the peritoneal dialysis must be taken seriously [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…20 The present study translates these prior findings of peritoneal membrane protection using the currently most accepted surrogate parameter of mesothelial cell status. 21 Importantly, these data are the first to demonstrate an increase of CA-125 on top of a dual-chamber PDF containing low glucose degradation products and physiologic pH.…”
Section: Discussionmentioning
confidence: 77%
“…[32][33][34][35] Therefore, an international consortium has recently proposed ex vivo-stimulated cytokine secretion assays from peritoneal cells as currently best biomarkers to monitor risk of peritonitis. 21 Previous studies have demonstrated depressed stimulated cytokine release from peritoneal cells obtained at early dwell times. 19,36 Importantly, at that time, conversion from migration of bacteria (e.g., after touch contamination) to infection may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The prolonged exposure to conventional PDS has been demonstrated to substantially contribute to peritoneal membrane injury and chronic low-grade inflammation 26 and a number of biomarkers have been evaluated in an attempt to help improve PD patient outcomes. 27 Acidic pH, high glucose concentrations and high levels of glucose degradation products in PDS have all been reported to cause local inflammation with resultant adverse functional outcomes, such as higher peritoneal solute transport rate (PSTR) and membrane failure due to fibrosis. Therefore, more bio-compatible PDS were developed aimed at mitigating some of these adverse effects.…”
Section: Discussionmentioning
confidence: 99%